The Development of a Business-Processes Model for the Quality Management System in the Hotels - SKOBKIN, Sergey Sergeevich; KOVALTCHUK, Andrey Pavlovich; BELAVINA, Yana Andreevna; KALITA, Gleb Vadimovich (Journal of Environmental Management and Tourism, 2017)
The current study seeks to extend our understanding of service quality by assessing a model of QMS that includes technical quality and functional qualities, as well as business processes, which should be modernized through the its development. The authors conducted a survey of representatives of the hotel business community located in Moscow (3-5-star hotels) and its clients to assess the most significant business processes, in terms of their impact on the quality of hotel services. As the study showed, representatives of the hotel business community support the division of business processes into four groups: key business processes; supporting business processes business management processes and business development processes, each of which has its own distinctive features.